ANALISIS KESULITAN SISWA KELAS X SMK BINA INSAN BANGSA DALAM MENYELESAIKAN SOAL CERITA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Doni Suharto Putro; Wahyu Setiawan (Journal on Education, 2019)
The main objective of this study was to examine the difficulties of students in solving SPLDV story problems. This study used a qualitative descriptive method. The subjects of this study were 26 students of class X of Bina Insan Bangsa (BIB) Vocational School Ngamprah 2018-2019. This study intends to determine the low ability of students to solve SPLDV story problems and provide alternative solutions. From the results of the tests it is known that the basic concepts in the SPLDV student story problems are still lacking so that there are errors in solving the questions. Thus it is known that the most difficulties that students do are the difficulty of changing the story questions into mathematical sentences with a percentage of 8.4%. So from that the giving of questions and exercises is very important to do to encourage students to develop their thinking patterns and can do the questions carefully.